Greenhouse Gases - Llamas Moya, Bernardo; Pous, Juan (IntechOpen, 2016)
Sustainability should be a key component of every process, safeguarding resources and reserves for future generations. This book shows how a responsible use of resources is possible, offering valid technological alternatives to fight climate change. We offer current technologies and valid methods for a wide range of activities: teaching, investigation, work, business and even daily life. We encourage all our readers to join us and become part of the solution to climate change, rather than the problem. After reading this book, we are certain that you will find justified reasons to start your own personal and social awareness campaign in favour of these effective technologies against climate change.